Integrated Curriculum Development Management in Forming the Spirituality and Intellectuality of Students: Case Study at the Roudhatul Muta'abbidin Islamic Boarding School in Sleman, Special Region of Yogyakarta - Abidin, Zainal (Al-Jadwa: Jurnal Studi Islam, 2022)
Islamic boarding schools are a type of complementary religious education institution for formal educational institutions and a form of transforming Islamic values ​​to Islamic generations. The demands of the times and society require innovation. Educational innovation concerns hardware and software aspects of Islamic boarding schools, so that students are not out of date. This research study uses a type of field research and uses a descriptive-qualitative paradigm. The data collection used is the method of observation, interviews, comments. The collected data is then analyzed using data collection methods, data presentation, data reduction, data verification. The results of this study indicate that the Roudhatul Muta'abbidin Islamic Boarding School in shaping the spirituality and intellectuality of the students with integrated curriculum management requires planning, implementation and evaluation. Curriculum planning in shaping the spiritual and intellectual intelligence of students at the Roudhatul Muta'abidin Islamic Boarding School is based on the motto, vision, mission and objectives of the pesantren. The implementation of an integrated curriculum at the Roudhatul Muta'abbidin Islamic Boarding School in shaping the spirituality and intellect of the students is carried out together with the Head of Dirosahan in making curriculum programs at the class level, Islamic boarding school curriculum and class level Permendiknas curriculum as well as activities outside the classroom, as well as conducting curriculum development for all asatidz through work meeting. While the curriculum evaluation carried out by the Raudhatul Muta'abbidin Islamic Boarding School is based on several things, namely based on needs and suitability, based on proposals based on semester exam results, observations made by the homeroom teacher and other assistants.